2016
DOI: 10.1007/s00520-016-3409-6
|View full text |Cite
|
Sign up to set email alerts
|

Severe drug interactions and potentially inappropriate medication usage in elderly cancer patients

Abstract: Nearly one third of the elderly cancer patients are exposed to severe drug interactions and PIMs. Clinicians dealing with elderly cancer patients should be more cautious when prescribing/ planning drugs to this group of patients. More strategies should be developed in this group of patients to minimize the medications prescribed and prevent severe DIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 20 publications
1
35
1
2
Order By: Relevance
“…Several previous studies simultaneously assessed polypharmacy, PIM use, and DDIs in older adults with cancer. Alkan et al reported frequencies of 30.8% polypharmacy, 35.1% severe drug interactions, and 26.6% PIM use in 445 older patients with cancer (286 outpatients and 159 inpatients). Only 38.1% of the participants had metastatic cancer in this study, and approximately 30% of the patients did not receive chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies simultaneously assessed polypharmacy, PIM use, and DDIs in older adults with cancer. Alkan et al reported frequencies of 30.8% polypharmacy, 35.1% severe drug interactions, and 26.6% PIM use in 445 older patients with cancer (286 outpatients and 159 inpatients). Only 38.1% of the participants had metastatic cancer in this study, and approximately 30% of the patients did not receive chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we assessed potential DDIs during the period of chemotherapy. DDIs were screened using the well‐validated clinical software system Lexi‐comp Drug Interactions (Lexi‐Comp, Inc., Hudson, OH) and reviewed by a clinical pharmacist. This system categorizes DDIs into five subgroups and provides clinical recommendations.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Potentially inappropriate medications (PIMs) are classes of drugs whose risks may potentially outweigh their benefits [1]. Despite evidence of negative outcomes in older adults, healthcare practitioners continue to prescribe PIMs [2] to the extent that it has now become a public health concern because of its association with increased morbidity, hospitalization, and mortality [3][4][5][6]. The prevalence of PIM use in older adult populations in both developed and developing countries is very high.…”
Section: Introductionmentioning
confidence: 99%
“…Outro achado significativo foi a maior taxa de interação medicamentosa no grupo de pacientes que utilizavam ao menos uma droga inapropriada (p < 0,001), assim como descrito na literatura. 8, 30 Diante das limitações metodológicas deste estudo (observacionais e transversais), não é possível estabelecer riscos objetivos associados às condições estudadas em algumas das variáveis analisadas, porém observa-se uma tendência de significância dos achados, dada a semelhança dos resultados com vários outros estudos da literatura. conclusão Na população estudada, a presença de polifarmácia foi de 56,5% e a de MPI, 46,5%.…”
Section: Resultsunclassified